Evaluation of Different Groundnut Arachis hypogea L. Cultivars Against Termites, Odontotermes obesus (Rambur) in Rawalpindi, Pakistan - Muhammad Usman Malik; Humayun Javed; Mahmood Ayyaz (Turkish Journal of Agriculture: Food Science and Technology)
Six groundnut (Arachis hypogea L.) cultivars i.e. Golden, BARI-2000, Australian, BARD-479, ICG-7326 and 2KCGC20 were evaluated against the attack of Odontotermes obesus in terms of percentage infestation of workers and soldiers, their damage and impact on the yield. The maximum mean populations of O. obesus workers were recorded on 2KCGC20 (30.82±2.75 workers/plot) and Australian (30.65±2.92 workers/plot), followed by BARI 2000 (19.55±2.51 workers/plot), Golden (17.30±2.27 workers/plot) and BARD-479 (16.82±2.06 workers/plot). The minimum mean population of O. obesus workers was found on ICG-7326 cultivars (14.85±1.81) workers/plot. The maximum mean population infestation of O. obesus soldiers was recorded on 2KCGC20 cultivar (4.88±0.25 soldiers/plot) followed by Australian (4.15±.30, soldiers/per plot), BARD-479 (2.00±.17 soldiers/plot), ICG-7326 (1.70±.14 soldiers/plot), BARD 2000 (2.40±.25 soldiers/ plot). The minimum mean population of O. obesus soldiers was found on Gold (1.87±.17 soldiers/plot). Population of O. obesus workers was positively related with the damage and negatively related the yield in all the groundnut cultivars.